The evolution of neutral hydrogen over the past 11 Gyr via H i 21 cm absorption. Issue 1 (20th August 2020) - Grasha, Kathryn; Darling, Jeremy; Leroy, Adam K; Bolatto, Alberto D
ABSTRACT: We present the results of a blind search for intervening H i 21 cm absorption towards 260 radio sources in the redshift range 0 < z < 2.74 with the Green Bank Telescope. The survey has the sensitivity to detect sub-damped Ly α (DLA) systems for H i spin temperatures Ts / f = 100 K, and despite the successful re-detection of 10 known 21 cm absorbers in the sample, we detect no new absorption lines in the full survey. Sources detected in 21 cm absorption were also searched for hydroxyl (OH) 18 cm absorption and we re-detect 1667 MHz OH absorption towards PKS 1830-211. We searched for intervening H i 21 cm absorption along the line of sight in each source achieving a total redshift coverage of Δ z = 88.64 (comoving absorption path of Δ X = 159.5) after removing regions affected by radio frequency interference. We compute a 95 per cent confidence upper limit on the column density frequency distribution f ( N H i ) and set a statistical constraint on the spin temperature T s in the range 100–1000 K, consistent with prior redshifted optical DLA surveys and H i 21 cm emission observations at the same redshifts. We infer a value for the cosmological mass density of neutral gas, ΩH i . Through comparison with prior ΩH i measurements, we place a statistical constraint on the mean spin temperature of T s / f = 175 K. Our derived ΩH i values support a relative mild evolution in ΩH i over the last 11 Gyr and are consistent with other methods that measure ΩH i .